Global corporate bond markets and local monetary policy transmission - Benlialper, Ahmet (Journal of Corporate Finance, 2026)
When tight monetary policy curtails domestic supply of credit and raises domestic borrowing costs, some firms can mitigate higher local borrowing costs by tapping global bond markets. This paper investigates whether this prediction holds for non-financial companies in the euro area. I first show that euro area firms exploit borrowing cost differentials between USD and EUR by issuing corporate bonds in USD when swap-adjusted U.S. dollar funding costs fall below euro rates. Using proxies for such opportunistic borrowing behavior, I then find that firms capable of seizing these opportunities in global corporate bond markets do not reduce their fixed capital investment to the same extent as other firms in response to monetary tightening. Further findings reveal that this differential investment response is not explained by differences in financial constraints or investment opportunities; instead, it reflects the ability to switch to lower cost offshore bond finance. Overall, the results underscore heterogeneity in the real effects of monetary policy and suggest that capital market openness can attenuate the domestic investment channel when global conditions allow lower cost funding abroad.